O Banco imobiliário, um jogo geográfico - Marie-Françoise Fleury; René Somain (Confins)
Monopoly is a universally known parlour game, with multiple national versions. French Monopoly is played on a board evoking the streets of Paris, going back to 1935. Is this real estate geography of the Thirties still valid? The authors propose a new version of the Parisian Monopoly, more faithful to the real social hierarchy than the current version and the newly released versions.